Students' Cognitive Load on Computer Programming Instructional Process Using Example-Problem-Based Learning and Problem-Based Learning Instructional Model at Vocational High School - Herlambang, Admaja Dwi; Ramadana, Muhammad Rifqy; Wijoyo, Satrio Hadi; Phadung, Muneeroh (Elinvo (Electronics, Informatics, and Vocational Education), 2024)
This paper fills an essential gap in applying cognitive load theory in teaching computer programming within vocational settings. It is an important area to consider for improving students' learning processes who intend to enter the rapidly changing technology sector. This study assessed the distinct impacts of the instructional paradigms, specifically Example-Problem-Based Learning (EPBL) and Problem-Based Learning (PBL), on students' cognitive loads upon framing an iterative structure lesson on computer programming. Vocational programming education is chosen for this purpose because vocational education faces unique challenges in integrating practical skills development with theoretical understanding, and programming tasks involve high cognitive demands. In a quasi-experimental design, 68 vocational high school students were assigned to an EPBL (n = 34) and a PBL (n = 34) group. The measurement of ICL was operationalized by RPI, the ECL by ME, and the GCL by LO. The relationship among the various components of the cognitive load was tested using the Spearman correlation test. There are significant differences in the profile of cognitive load between the two groups: the EPBL group was always associated with the lower ECL and higher GCL. In other words, the present study is original because it systematically compares EPBL with PBL in the context of vocational programming education and provides empirical evidence based on instructional design decisions. These findings suggest a further refinement of the CLT within domain-specific contexts and practical guidelines for optimizing instructional strategies in computer programming education in vocational schools.